Analisis Proses Pembuktian Penguasaan Narkotika Yang Disimpan Di Dalam Meja Rias Kamar Tidur Suami dan Istri : (Studi Kasus Putusan Perkara No. 303/Pid.Sus/2023/PN.Kag) - Maulana, Rizki; Rifai, Anis; Suartini, Suartini (Jurnal Bedah Hukum, 2025)
Abstract The crime of trafficking and abuse of narcotics is a crime that often occurs in Indonesia. The role of the Public Prosecutor in prosecuting and proving the criminal offenses charged is very important. There are issues that often occur, including the law enforcement process for narcotics crimes and the evidentiary process for defendants who store narcotics in the husband and wife's bedroom, where the occupants of the house are often arrested and made suspects due to the discovery of narcotics evidence, so an analysis of proof of possession is needed. Narcotics in the bedroom are outlined in this article using Normative Juridical research methods as well as a case approach and primary legal materials in answering the problems regarding this research. The results of the research explain that regarding narcotics stored in the husband and wife's bedroom without permission from the Ministry of Health, the process of proving ownership of narcotics by the Public Prosecutor in case NO.303/Pid.Sus/2023/PN.Kag, the Panel of Judges believes has been fulfilled. elements in Article 114 paragraph (2) in conjunction with Article 11 and Article 7 of Law no. 35 of 2009 concerning Narcotics which is strengthened by the presence of 2 (two) pieces of evidence based on Article 184 of the Criminal Procedure Code and witnesses, so that the Defendant deserves to be convicted. Abstrak Tindak pidana peredaran dan penyalahgunaan Narkotika merupakan kejahatan yang kerap terjadi di Indonesia. Peran Jaksa Penuntut Umum dalam mendakwakan dan pembuktian terhadap tindak pidana yang didakwakan sangat penting. Terdapat isu masalah yang kerap terjadi, diantaranya adalah proses penegakan hukum tindak pidana narkotika dan proses pembuktian bagi terdakwa yang menyimpan narkotika didalam kamar tidur suami dan istri, dimana penghuni rumah kerap ditangkap dan dijadikan tersangka karena ditemukannya barang bukti narkotika, maka dibutuhkan analisis terhadap pembuktian penguasaan narkotika didalam kamar tidur tersebut yang dituangkan dalam artikel ini dengan menggunakan metode penelitian Yuridis Normatif serta pendekatan kasus dan bahan hukum primer dalam menjawab permasalahan mengenai penelitian ini. Hasil penelitian menerangkan terhadap Narkotika yang disimpan dalam kamar tidur suami dan istri yang tidak disertai ijin dari Kementerian Kesehatan adalah tindak pidana, maka terhadap proses pembuktian kepemilikan Narkotika oleh Penuntut Umum dalam perkara NO.303/Pid.Sus/2023/PN.Kag, Majelis Hakim meyakini telah terpenuhi unsur-unsur dalam Pasal 114 ayat (2) jo Pasal 11 dan Pasal 7 UU No. 35 Tahun 2009 tentang Narkotika yang dikuatkan dengan adanya 2 (dua) alat bukti berdasarkan Pasal 184 KUHAP dan saksi-saksi, sehingga Terdakwa patut untuk dipidana.